Saposin D acting on macrophage bacteriostatic function in experimental tuberculosis infection - G. S. Shepelkova (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
The protection against tuberculosis infection is largely determined by the ability of host tissue macrophages to limit the growth and spread of mycobacteria. Able to multiply within the host macrophages, mycobacteria have developed a number of protective mechanisms preventing phagosome-lysosome fusion, thereby evading damaging effects of lysosomal enzymes. Saposins are small, acidic, thermostable, non-enzymatic glycoproteins that participate as co-fac-tors in degradation of short oligosaccharide head group glycosphingolipids. Saposins A, B, C and D are formed in acidic endosomes due to cleavage of initial prosaposin molecule. The effect of saposins on human immune response is mediated by their involvement in presenting mycobacterial antigens on CD1 molecules. Preliminary studies with electron microscopy allowed to uncover saposin D-bound damaging effect on Mycobacterium tuberculosis in acidic environment. These data allowed us to suggest that saposin D is an important protective component fighting against TB infection. The aim of the study was to explore how saposin D deficiency might affect formation of anti-tuberculosis immune response and ability of macrophages to inhibit M. tuberculosis growth. Materials and methods. Interstitial pulmonary macrophages and peritoneal macrophages were isolated from wild type C57BL/6 strain and saposin D deficient C57BL/6-SapD-/- mouse strains. Results. It was found that as compared to macrophages from mice, macrophages from wild type strain significantly better controlled mycobacteria growth in vitro. To study an opportunity of compensating for deficient saposin D in peritoneal macrophages from C57BL/6-SapD-/- mice, a saposin D gene-bearing lentiviral vector was created. Transfection of SAPD-deficient peritoneal macrophages with expression vector compensated for saposin D deficiency in such cells and restored bactericidal function. The mechanisms of action for current anti-TB drugs are mediated by various metabolic pathways in mycobacteria (inhibited biosynthesis of fatty acids, arabinogalactan, peptidoglycan and protein; inhibition of DNA-dependent processes, proton pumps and cytochrome P450-dependent monooxygenases). Conclusion. It was shown that saposin D deficiency affects activation of macrophage bactericidal function in vitro. Our study data may be a prerequisite for biologically substantiated potential of using a vector construct bearing natural human protein gene such as saposin D, as a new anti-tuberculosis drug.